Absence of exaggerated pharmacology by recombinant ADAMTS13 in the rat and monkey. Issue 1 (January 2022) - Rossato, Paolo; Glantschnig, Helmut; Leidenmühler, Peter; Kopic, Alexandra; Ruthsatz, Tanja; Majer, Bernhard; Schuster, Maria; Scheiflinger, Friedrich; Höllriegl, Werner
Abstract : N/A: Insufficiency of ADAMTS13 (a disintegrin and metalloprotease with thrombospondin motif repeats-13) is the cause of thrombotic thrombocytopenic purpura (TTP) and contributes in microangiopathy in sickle cell disease (SCD). Recombinant ADAMTS13 effectively cleaves prothrombotic ultra-large von Willebrand factor (VWF) multimers. It is being tested as replacement therapy for TTP, and at supra-physiologic concentrations, for moderating vaso-occlusive crisis in SCD. Deficiencies of VWF, or concomitant treatment with antithrombotic drugs, could pose risks for increased bleeds in these patient populations. The purpose of the experiments was to evaluate the potential of exaggerated pharmacology and temporary bleeding risks associated with rADAMTS13 administration. We utilized safety studies in monkey and tested the effects of administering maximum-feasible doses of rADAMTS13 on nonclinical safety and spontaneous or aggressive bleeds in the rat model. Evaluation of pharmacokinetics, toxicity profiles, and challenge in a tail-tip bleeding model show that treatment with rADAMTS13 did not increase bleeding tendency, either alone, or in combination with enoxaparin or acetylsalicylic-acid. These novel findings demonstrate absence of rADAMTS13 exaggerated pharmacology without spontaneous or aggravated bleeds even at supra-physiologic (>100-fold) plasma concentrations.